MENELADANI METODE DAN KARAKTERISTIK NABI MUHAMMAD DALAM MENGAJAR AL QURAN - Refna An Adella; Zainuddin Fanani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The book ‘Rasulullah Sang Guru’ (The Prophet Muhammad, the Teacher) by Abdul Fattah Abu Ghuddah is the main source of research on the application of the Qira'ati method. From an Islamic perspective, a teacher is seen as an educator who strives to develop the full potential of their students. To be a good role model for their students, teachers must have noble character and morals. In addition, teachers must show compassion and sincerity during the learning process so that students are motivated and enthusiastic to become active, creative, and innovative individuals. This study used a descriptive qualitative approach with the research subjects being TPQ principals and Qira'ati teachers. Data collection was carried out through observation, interviews, documentation, and triangulation, while data analysis included data presentation, data reduction, and verification. The results of the study show that: 1) the application of the Prophet's characteristics in the Qira'ati method by teachers in the classroom has an effect on student learning development; 2) the application of the Qira'ati learning method, which adopts the Prophet's method, has a positive impact on student learning outcomes. Translated with DeepL.com (free version)